Opportunities and Challenges of Halal Cosmetics and its Contribution to Economic Sector in Indonesia - Rahmi, Asri Noer (Universitas Darussalam Gontor, 2024)
**English**This research aims to look at how the opportunities and challenges of halal cosmetics and it’s contribution in economic sector in Indonesia as well as consumers understanding of halal cosmetics and good for health. The study used the Theory of Planned Behavior model. The respondents in the study were owner one of halal cosmetic, customers active halal cosmetic and knew what type of cosmetics to use and did not have any negative effects in their use. The research method used is qualitative through interviews with cosmetic owner and customers both male and female. Consumers who have literacy and education related to the importance of halal cosmetics give a positive response and promote the use of halal labeled cosmetics, while consumers who still lack literacy and education of halal cosmetics are still interested in using cosmetics that have not been labeled halal at affordable prices, or are foreign cosmetics that are not yet clear. Opportunities and challenges faced by halal cosmetics in Indonesia include education and literacy, affordable product prices and support from the government and halal certification in Indonesia. **Indonesia**ekonomi di Indonesia serta pemahaman konsumen atas kosmetik halal dan baik bagi kesehatan. Penelitian ini menggunakan model Theory of Planned Behavior. Responden dalam penelitian ini adalah salah satu pemiliki kosmetik halal, pengguna kosmetik aktif dan mengetahui jenis kosmetik apa yang harus digunakan dan tidak memberikan efek negatif dalam penggunaannya. Metode penelitian yang digunakan adalah kualitatif melalui interview dengan konsumen pengguna kosmetik baik laki-laki maupun perempuan. Konsumen yang memiliki literasi dan edukasi terkait pentingnya kosmetik halal memberikan respon positif dan mempromosikan penggunaan kosmetik berlabel halal, sedangkan konsumen yang masih kurang literasi dan edukasi kosmetik halal masih tertarik menggunakan kosmetik yang belum berlabel halal pada harga terjangkau, atau merupakan kosmetik luar negeri yang belum jelas kehalalannya. Peluang dan tantangan yang dihadapi kosmetik halal di Indonesia diantaranya edukasi dan literasi, harga produk yang terjangkau dan adanya dukungan dari pemerintah dan sertifikasi halal di Indonesia.